Performance of dense graded asphaltic concrete using nanosilica modified bitumen - A. K., Arshad; E., Shaffie; K. A., Masri; W., Hashim; Z. A., Rahman (IOP Publishing, 2019)
Flexible pavements are constructed to last for its design life, therefore, a good and durable asphalt surface layer is required. However, flexible pavements using dense graded asphaltic concrete have some shortcomings such as prone to rutting when heavy loads are applied at high ambient temperatures. One of the ways to improve the performance of dense graded asphaltic concrete is to modify the bitumen using nanosilica. Among the properties of nanosilica that is advantageous to improve the bitumen is strong absorption, large surface area and excellent stability. The objective of this study is to investigate the use of nanosilica as a bitumen modifier to improve the moisture susceptibility and rutting resistance of dense graded asphaltic concrete. Bitumen PEN 60/70 was modified with nanosilica at 2% by weight of bitumen. The performance of the asphaltic concrete specimens was then evaluated in terms of its moisture susceptibility, resilient modulus and rutting resistance. The results obtained from the testing showed that the addition of nanosilica increased the resilient modulus value and reduced the rutting depth of dense asphaltic concrete mixes, while achieving the required moisture resistance. It concludes that the addition of nanosilica in the bitumen improved the performance of dense asphaltic concrete mix.